Bringing Forth Within: Enhabiting at the Intersection Between Enaction and Ecological Psychology - James, Mark M. (Frontiers in Psychology, 2020)
Baggs and Chemero (2018) propose that certain tensions between enaction and ecological psychology arise due to interpretations about what is meant by the ‘environment’. In the enactive approach the emphasis is on the umwelt, which describes the environment as the “meaningful, lived surroundings of a given individual”. The ecological approach, on the other hand, emphasises what they refer to as the habitat “the environment as a set of resources for a typical, or ideal, member of a species”. By making this distinction, these authors claim they are able to retain the best of both the ecological and the enactive approaches. Herein I propose an account of the individuation of habits that straddles this distinction, what I call a compatabilist account. I do this in two parts. In the first part I tease out a host of compatibilities that exist between the enactive account as developed by Di Paolo et al. and the skilled intentionality framework as developed by Rietveld et al. In the second part, I suggest that these compatibilities can be brought together with the philosophy of Gilbert Simondon to develop the notion of enhabiting. Enhabiting describes the processes by which the habitat is effectively transformed into the umwelt. What the account of enhabiting highlights, is that affordances in the habitat can help drive the resolution of tensions in the umwelt of a given subject, leading to its transformation. Thus, enhabiting points towards a point of intersection between enaction and ecological psychology. To enhabit is bring forth (to enact), within (to inhabit).